Knowledge, Attitude And Practice Of Diabetes Mellitus; A Comparative Study Between Malaysian And The United Arab Emirates Patients - Mahdi, Hala Jehad (2010)

(untitled)
Diabetes mellitus is an emerging health problem worldwide, the prevalence varies widely in different regions around the world. It is well known that good diabetes education is a cornerstone of diabetes control. Some studies of different health education programs in Malaysia and the United Arab Emirates (UAE) have shown that diabetics in these countries generally know less about the disease and its management than diabetics in other countries.